Controle da finalidade dos tributos extrafiscais enquanto garantia fundamental do contribuinte - Fortaleza, Felipe de Abreu (2021)
This work analyses the possibility, in brazilian law, of control over acts and decrees about the percentage of extrafiscal taxes, based on the idea of deviation of extrafiscal purpose. This is an investigation of the concept of extrafiscality, of the arguments used in the “Ações Diretas de Inconstitucionalidade” (ADI) 4.002, 4.004 and 4.110 and in the “Arguição de Descumprimento de Preceito Fundamental” (ADPF) 772, as well as the safeguards of the tax payer against inappropriate charges of extrafiscal taxes, in particular of those which do not follow strict tributary legality, together with the decrees that raise their percentage. The last part of the work analyses technical and procedural aspects of the control of extrafiscality. The methodology is bibliographical and documental; references to the documents of the aforementioned lawsuits, to the precedents of the superior courts, to the specialized doctrine and to the literature about extrafiscality are made. The work concludes that, even though the institution and charging of any tax has extrafiscal consequences, it is possible to identify extrafiscal taxes, measures and policies stricto sensu. Those, provided that there is a constitutional rule which bind them to extrafiscality, can have their finality controlled by the Judiciary, including by means of constitutional jurisdiction. Finally, the work concludes that the deviation of extrafiscal purpose is a constitutional offense and that the tax payer has, as a constitutional safeguard, the possibility of control of said purpose.